RANCANG BANGUN SISTEM NAVIGASI PADA DIFFERENTIAL STEERING MOBILE ROBOT - Prabowo, Yanuhar; Widyantara, Helmy; Susanto, Pauladie (Journal of Control and Network Systems, 2014)
Abstract: In general, a system is composed of several sub-systems that support the system so it can function perfectly as planned. A system that helps people to monitor gas consists of sub-systems that are equipped with gas sensors and other sensors.This study analyzed the design of navigation systems on the differential steering mobile robot, a robot moving (mobile robots) that can be programmed to move towards a certain point coordinates. This Mobile Robot System is a sub-system which supports the Gas Monitoring system. This study uses the method of analysis of literature study of the theories in the book, the data from each of the components as well as articles from the internet. Based on the theories and these data, we design hardware, testing hardware, software manufacture, integrating all sub-systems into a mobile robot system, testing the overall functionality.Â Modules, components used in the design of mobile robots, among others: microcontrollers ATmega128; DT-AVR ATmega1280 CPU MODULE; Differential Mover Robot; DAGU Rover 5 4WD; CMPS10 Tilt Compensated Magnetic Compass; Rotary Encoder; DC motors; Motor controllers; and Liquid Cristal Display ( LCD ). Designing program that are used in the planning of the mobile robots, among others, for the purpose of determining the direction of the coordinates using the application of the theory of trigonometry, the distance to the determination of the coordinates of the destination using the application of the theory of Pythagoras.These results indicate that the design of navigation system of differential steering mobile robot was successful with insignificant error of totally system testing. These results of totally navigation system testing indicate error average amount 0.14 coordinates or amount 3.29 cm.Keyword: microcontroller, navigation system, trigonometry, Pythagoras, differential steering mobile robot.